THE IMPACT OF GENDER DIVERSITY, PROFITABILITY, LEVERAGE AND FIRM SIZE ON FIRM VALUE IN COSMETICS AND HOUSEHOLD NEEDS COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Tuerah, Kekee Marisa; Rumokoy, Lawren J.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2024)
This study aims to find out the impact of Gender Diversity, Profitability, Leverage and Firm on Firm Value in Cosmetics and Household Needs Companies Listed on Indonesia Stock Exchange. Quantitative method used in this research with a panel data regression analysis research model. Secondary data are the main source. The sampling techniques used was nonprobability selection approach. The sample utilized unbalanced panel data, throughout the period from 2018-2022, a total of 37 samples were collected and analyzed for this study. The result of this study indicate that partially Gender Diversity and Profitability has a positive relationship but statistically insignificant impact on Firm Value in Cosmetics and Household Needs Companies Listed on IDX, partially Leverage and Firm Size indicating a negative relationship and insignificant impact on Firm Value in Cosmetics and Household Needs Companies Listed on IDX, and simultaneously Gender Diversity, Profitability, Leverage and Firm Size have no significant impact on Firm Value in Cosmetics and Household Needs Companies Listed on IDX. Keyword: Gender Diversity, Profitability, Leverage and Firm Size